Enhancing Inclusive Education through Learning Management System (LMS): Prospects, Challenges and Perspective at the School Level - Shukla, Priyanka; Pandey, Yogendra (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2026)
The integration of ICT tools, particularly learning management systems (LMS), has transformed traditional teaching and learning practices. They are recognized as being important resources for the educational system. The value of inclusive education, which aims to give all students equal access to learning opportunities regardless of their various origins and skills, is extremely high in today's educational approaches. Nowadays, many higher education institutions are now provided with Learning Management Systems (LMS) to deliver comprehensive online learning solutions and to utilize its features and capabilities to improve learning practices. As a result of the rapid advancement of technology, Learning Management Systems (LMS) have evolved into flexible tools capable of improving efforts at inclusive education. This study investigates the potential and challenges of utilizing LMS to improve inclusive education and provides perspectives from school-based teachers. By examining the perspectives of teachers, this study reveals the practical consequences, awareness, accessibility, challenges, and issues, and associated with installing LMS in inclusive classrooms. The main aim of the study of focusing more closely on the use of LMS for students with special needs is to put equality, diversity, and inclusive education into practice. The current study intends to develop an understanding of the LMS from the perspective of teachers, explore the use of its functionalities, and identify the barriers that may influence LMS utilization at the school level in the Varanasi district.